Respuesta :
2(3x-10)+8x=7x+20+7
We move all terms to the left:
-2(3x-10)+8x-(7x+20+7)=0
We add all the numbers together, and all the variables
-2(3x-10)+8x-(7x+27)=0
We add all the numbers together, and all the variables
8x-2(3x-10)-(7x+27)=0
We multiply parentheses
8x-6x-(7x+27)+20=0
We get rid of parentheses
8x-6x-7x-27+20=0
We add all the numbers together, and all the variables
-5x-7=0
We move all terms containing x to the left, all other terms to the right
-5x=7
x=7/-5
x=-1+2/5
We move all terms to the left:
-2(3x-10)+8x-(7x+20+7)=0
We add all the numbers together, and all the variables
-2(3x-10)+8x-(7x+27)=0
We add all the numbers together, and all the variables
8x-2(3x-10)-(7x+27)=0
We multiply parentheses
8x-6x-(7x+27)+20=0
We get rid of parentheses
8x-6x-7x-27+20=0
We add all the numbers together, and all the variables
-5x-7=0
We move all terms containing x to the left, all other terms to the right
-5x=7
x=7/-5
x=-1+2/5